Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Hasil Belajar IPA Siswa - Asmara, Dedi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to determine the increase in learning outcomes of science material special characteristics of living animals using jigsaw learning methods in grade VI students of SD Negeri 06 Sialang, Kapur IX District, Lima Puluh Kota District. This research is an experimental research in the form of Classroom Action Research (CAR) with the subjects in this study being class VI students totaling 24 students. Data collection techniques in this study are; (1) observation of teacher activity, (2) observation of student activity, and (3) test of learning outcomes. Based on the results of the study found an increase in the average value of the class of research subjects rose from the pre-cycle average value of 74.16, cycle I 79.58 to 87.08 in cycle II and PTK was considered successful. Conclusions, based on the results of the study, the jigsaw method can improve science learning achievement in grade VI students with special characteristics of animal living things in SD Negeri 06 Sialang, Kapur IX District, Lima Puluh Kota. Keywords: Learning Outcomes, Cooperative Learning Methods, Jigsaw Learning